Pengembangan Kurikulum Berbasis Keterampilan Abad ke-21 untuk Pendidikan Inklusif di Sekolah Dasar - M Luthfi Oktarianto; Sofiya Ramadhani (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Curriculum development in education is a complex and continuous process aimed at designing an effective learning plan for students. Principles in curriculum development, such as responsiveness to student needs, relevance to the demands of the times, inclusivity, and stakeholder participation, serve as the foundation for determining the direction and objectives of the curriculum. This study uses a descriptive qualitative approach, utilizing data from relevant literature to investigate the implementation of these principles in curriculum development. The results show that the implementation of an inclusive curriculum responsive to the demands of the times faces several challenges, including student diversity, the relevance of the curriculum to technological advancements, and alignment with societal expectations. Collaborative efforts from various stakeholders are necessary to continuously improve the curriculum to meet students' needs more effectively, enabling them to face future challenges more effectively.